Role of online education in building brand image of educational institutions - Manhas, Parikshat S. (2012)
In this article we try to present the general impression that online learning/real time virtual learning conveys. The myriad interpretations of online education are depicted elaborately along with its advantages and influence on various stakeholders. The disadvantages of online education reveal their apparently potent drawbacks, which are then trailed by «opposing views». These views give concrete justifications against the so-called shortcomings of online learning and enlist the techniques used to tackle them. Besides of what online education does for students, learners and tutors at large, it also confers some potential by-products, such as helping build a strong brand image of educational institutions that offer it. Although educational institutions worldwide are employing online learning resources to create a brand image for themselves, a well-worn discussion has to be mooted to understand the implications of their usage.